Plastics for dinner: Store-bought seafood, but not wild-caught from the Great Barrier Reef, as a source of microplastics to human consumers - Amanda L. Dawson; Joan Y.Q. Li; Frederieke J. Kroon (Environmental Advances, 2022)
Seafood accounts for more than 17% of the global consumption of animal protein, with an excess of 335000 t consumed in Australia throughout 2019-2020. Recently, the presence of microplastics (MPs) within commercial seafood and the potential vectorisation of MPs to human consumers has become a significant concern for the public and the scientific community. Here, four commonly harvested wild-caught marine organisms were assessed for MP presence. These species comprise a significant proportion of the Queensland seafood industry, as well as being highly desirable to Australian consumers. The edible muscle tissue and discarded digestive tissue (GIT) of barramundi (Lates calcifer), coral trout (Plectropomus leopardus), blue leg king prawns (Melicertus latisulcatus), and Ballot's saucer scallops (Ylistrum balloti), were analysed discretely to determine the extent to which these species may be contaminated in the wild (GIT tissue), and the extent to which they themselves may act as a vector for human exposure (edible muscle tissue). Wild-caught seafood was predominantly free of MPs, with digestive tissues from two of ten coral trout containing only two fibres each. All wild-caught muscle tissue samples were free of MPs, as was the GIT of scallops, prawns, and barramundi. On the other hand, fresh, skinless barramundi muscle tissues, purchased from various commercial suppliers, were examined and found to be significantly contaminated with MPs (0.02 - 0.19 MP g-1). Overall, these results highlight the growing consensus that food can become contaminated simply by being prepared in the human environment, and the focus must shift to determining the extent of MP proliferation within the processing and point-of-sale environment.